2012
DOI: 10.1002/pc.22344
|View full text |Cite
|
Sign up to set email alerts
|

Nanoclay‐reinforced poly(butylene adipate‐co‐terephthalate) biocomposites for packaging applications

Abstract: Increasing generation and inadequate disposal of waste progressively compromise our environment. Solutions are proposed by the development of biodegradable polymers, that is, for short‐term applications like packaging. The present study focuses on the design and characterization of biodegradable poly(butylene adipate‐co‐terephthalate) (PBAT) nanocomposites reinforced by different types of nanoclays. The addition of natural and modified montmorillonite and bentonite to PBAT by melt mixing enhances slightly the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…This transition is attributed to the motion of poly(butylene adipate) units, the flexible aliphatic domain. The second one, at 50°C is ascribed to the motion of poly(butylene terephthalate) units, which is a rigid aromatic domain …”
Section: Resultsmentioning
confidence: 99%
“…This transition is attributed to the motion of poly(butylene adipate) units, the flexible aliphatic domain. The second one, at 50°C is ascribed to the motion of poly(butylene terephthalate) units, which is a rigid aromatic domain …”
Section: Resultsmentioning
confidence: 99%
“…For each material three specimens are tested. As PBAT has a very low degree of crystallinity , the degree of crystallinity Χ c of the polymer mixtures was calculated on the basis of the heat of fusion of the sample Δ H f , and of its weight fraction of PHBV Φ . The heat of fusion of 100% crystalline PHBV and PBAT are Δ H 0 = 109 J/g and 114 J/g, respectively : Xnormalc=ΔHnormalfΔH0Φ100. …”
Section: Methodsmentioning
confidence: 99%
“…Only Javadi et al investigated the influence of the polymer weight ratio of three commercial PHBV/PBAT blends in solid and microcellular materials . Functionalized OMMT turned out to be compatible with PHBV as well as with PBAT . Another studies reported on the improvement of properties by addition of nanoclay to PHBV and PBAT .…”
Section: Introductionmentioning
confidence: 99%
“…The biological degradation of PBAT has been thoroughly investigated [2][3][4]. PBAT can be used to produce fibers [5,6], textile, films [7] (such as mulching films) and packaging materials [8,9]. Moreover, PBAT composites and modified PBAT have been widely investigated in order to prepare value-added products, such as conductive [10] and antimicrobial materials [11][12][13][14][15][16], and meanwhile to minimize the cost.…”
Section: Introductionmentioning
confidence: 99%